Cover Image. (18th February 2022) - Cheng, Kang‐jie; Liu, Yun‐feng; Wang, Russell; Yuan, Zi‐xi; Jiang, Xian‐feng; Dong, Xing‐tao
Abstract: The cover image is based on the Basic Research Biomechanical behavior of mandible with posterior marginal resection using finite element analysis by Kang‐jie Cheng et al., https://doi.org/10.1002/cnm.3549 . Abstract : The cover image is based on the Basic Research Biomechanical behavior of mandible with posterior marginal resection using finite element analysis by Kang‐jie Cheng et al., https://doi.org/10.1002/cnm.3549 .